2020
DOI: 10.3390/nu12092703
|View full text |Cite
|
Sign up to set email alerts
|

Risk Reduction for End-Stage Renal Disease by Dietary Guidance Using the Gustatory Threshold Test for Salty Taste

Abstract: Educational hospitalization of patients with chronic kidney disease (CKD) may slow the progression of renal dysfunction. However, the educational aspect that is more effective has not been identified to date. In this study, patients with CKD were evaluated for gustatory threshold for salty taste and received augmented salt reduction guidance under educational hospitalization at Nagasaki University Hospital from October 2016. In total, 277 eligible patients were enrolled and hospitalized from 2012 to 2019 (mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…For example, in chronic kidney disease, high salt intake is among the top dietary risk factors for disease progression. Previous studies show that the evaluation of gustatory threshold for salty taste followed by patient education on their gustatory deficits to promote salt restriction was significantly associated with improvement in estimated glomerular filtration rate (eGFR) and lower dialysis induction rates 27 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in chronic kidney disease, high salt intake is among the top dietary risk factors for disease progression. Previous studies show that the evaluation of gustatory threshold for salty taste followed by patient education on their gustatory deficits to promote salt restriction was significantly associated with improvement in estimated glomerular filtration rate (eGFR) and lower dialysis induction rates 27 …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies show that the evaluation of gustatory threshold for salty taste followed by patient education on their gustatory deficits to promote salt restriction was significantly associated with improvement in estimated glomerular filtration rate (eGFR) and lower dialysis induction rates. 27 In an aging cohort, a correlation between taste and smell loss suggests involvement of multiple sensory pathways with aging and cognitive decline. In recent literature, Lang et al 16 examined 52 patients in a memory clinic and found a reduction in gustatory function in patients with dementing diseases, especially Parkinson syndromes, beyond that expected with normal aging.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have also supported that education on sodium intake improves salt sensation itself [ 9 , 10 ]. It was reported that educational hospitalization with enhanced salt reduction guidance reduced the risk of end-stage renal disease [ 13 ]. Sodium restriction seems to be effective under the control of nutritional status.…”
Section: Interaction Among Sodium Intake Appetite and Nutrition mentioning
confidence: 99%
“…Salt intake can be estimated by collecting urine over 24 hours (24 h urine), but, because this is difficult for both researchers and participants, it leads to incomplete data and low survey response rates; thus, spot urine is alternatively used to estimate salt intake [ 12 , 13 , 14 ], which is recommended by 2019 guidelines for the management of hypertension from the Japanese Society of Hypertension [ 15 ].…”
Section: Introductionmentioning
confidence: 99%